ChemInform Abstract: Four‐Component α‐Bromo‐β‐phosphoalkoxylation of Aromatic α, β‐Unsaturated Carbonyl Compounds. Issue 28 (July 2015) - Sohail, Muhammad; Zhang, Yixin; Liu, Wujun; Chen, Qin; Wang, Lei; Zhao, Zongbao K.
Abstract The four‐component α‐bromo‐β‐phosphoalkoxylation of aromatic α, β‐unsaturated carbonyl compounds is described.